Identification of lactic acid bacteria constituting the predominating microflora in an acid-fermented condiment (tempoyak) popular in Malaysia - Leisner, J.J; Vancanneyt, M; Rusul, G; Pot, B; Lefebvre, K; Fresi, A; Tee, L.K (Elsevier, 2001)
Tempoyak is a traditional Malaysian fermented condiment made from the pulp of the durian fruit (Durio zibethinus). Salt is sometime added to proceed fermentation at ambient temperature. In various samples obtained from night markets, lactic acid bacteria (LAB) were the predominant microorganisms, ranging from log 8.4 to log 9.2 cfu g−1. No other microorganisms were present to such a level. These samples contained reduced amount of saccharose, glucose and fructose but increased amount of d- and l-lactic acid and acetic acid compared with samples of non-fermented durian fruit. Sixty-four isolates of LAB were divided into five groups by use of a few phenotypic tests. A total of 38 strains of LAB were selected for comparison by sodium dodecyl sulfate–polyacrylamide gel electrophoresis (SDS–PAGE) of their whole cell protein patterns with a SDS–PAGE database of LAB. These strains were also examined for their carbohydrate fermentation patterns by use of API 50 CH. Isolates belonging to the Lactobacillus plantarum group were shown to be the predominant members of the LAB flora. In addition, isolates belonging to the Lactobacillus brevis group, Leuconostoc mesenteroides, Lactobacillus mali, Lactobacillus fermentum and an unidentified Lactobacillus sp. were also observed. A high degree of diversity among isolates belonging to the Lb. plantarum group was demonstrated by analysis of their plasmid profiles.